MECHANICAL PROPERTIES OF PALM KERNEL SHELL ASH BLENDED CEMENT CONCRETE - Amartey, Bilkisu Hassan Sada; Taku, Kumator Josiphiah; Amartey, Yusuf Dada (FUDMA JOURNAL OF SCIENCES, 2023)
Chemical and agricultural process industries generate substantial amounts of industrial by-products annually, leading to environmental pollution and escalating waste disposal expenses for the industry. As environmental awareness grows and landfill space becomes scarce, there is a rising interest in researching waste materials utilization. Exploring alternative methods, instead of disposal aims to minimize pollutions impact on the environment. The application of pozzolanic materials in construction works is on the rise, and this trend is anticipated to persist in the coming years, driven by the depletion of natural materials essential for manufacturing construction materials such as cement. This study investigates the utilization of agro-waste ash as a supplementary cementitious material SCM, specifically palm kernel shell ash (PKSA) as a substitute material for ordinary Portland cement (OPC) in concrete. Specimens containing 5, 10, 15, 20, 25 and 30% palm kernel shell ash (PKSA) as replacement for cement in the concrete were prepared at a water/binder ratio of 0.65. The results showed that the samples incorporating binary blends of cement with 5 – 15% PKSA illustrated better strength properties at ages above 28 days of hydration than that of control sample without PKSA. The compressive strength obtained were 26.76MPa, 26.81MPa and 27.16MPa at 60 days, and 29.80MPa, 30.0MPa and 31.41MPa at 90 days for 5 – 15% replacement levels respectively. The tensile strength values obtained were 4.5MPa, 4.5MPa and 4.7MPa at 60 days and 5.2MPa, 5.2MPa and 5.4MPa at 90 days for 5 – 15% replacement levels...